Development of new OCDMA encoder and decoder modules - Farah Hayati Che Lah (Universiti Malaysia Perlis, 2008)
A desirable feature for future optical networks would be the ability to process information directly in the optical domain for purposes of multiplexing, demultiplexing, filtering, amplification, and correlation. Optical signal processing would be advantageous since it can potentially be much faster than electrical signal processing and the need for photonelectron-photon conversion would be obviated. There has been a tremendous interest in applying Code Division Multiple Access (OCDMA) techniques to fiber optic communication systems. This technique is one of the multiple access schemes that are becoming popular because their advantages such as the flexibility in the allocation of channels, ability to operate asynchronously, enhanced privacy and increased capacity in bursty networks. Especially, direct detection OCDMA systems have been investigated widely to apply for high speed LAN, because they allow multiple users to access network simultaneously. In the case of data transfer where traffic tends to be bursty rather than continuous, CDMA can be used for contention-free, zero delay access. This project is concentrated on the design of encoder and decoder modules for OCDMA system based on Fiber Bragg Gratings (FBGs). The code used in this project is Modified Double Weight (MDW) which is developed in a family of the Double Weight (DW).